Tryptophan hydroxylase gene polymorphism in patients with obsessive-compulsive disorder - Korkmaz, Sevda; Onalan, Ebru; Yuce, Huseyin; Atmaca, Murad (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2016)
Objective: There is limited number of studies on the effects of tryptophan hydroxylase1 (TPH1) A218C gene polymorphism on obsessive-compulsive disorder (OCD) etiology. This study aims to scrutinize the role of TPH1-A218C gene polymorphism on OCD etiology. Methods: Sixty patients diagnosed with OCD, applied to our clinic and fitting the study criteria were accepted as patient group. A group of 60 healthy individuals matching the patient group in age and gender were selected as the control group. In the study the Clinical Interview Scale Structured for DSM-IV Axis-I Disorders, Socio-demographic and Clinical Data Form, Yale Brown Obsessive Compulsive Rating Scale (Y-BOCS) and Hamilton Depression Rating Scale were applied to participants initially. Consequently, they were classified into two groups of 'responsive to therapy' and 'resistant to therapy' based on their therapy histories and Y-BOCS points. For DNA isolation 300 mu l blood samples were used in compliance with standard methods. Restriction Fragment Length Polymorphism method was used to evaluate A218C polymorphism in TPH-1 gene within the blood samples. Results: No significant difference was observed between patient and control groups related to TPH-1 genotypes. However, a significant increase was observed in AA genotype frequency for TPH-1gene in the patient group resistant to therapy and in CC genotype frequency in the patient group responsive to therapy. The difference of the allele type ratios in this polymorphism between each patient group could be related to the response to therapy. To confirm the findings of the study, more research on the same gene polymorphisms is required with OCD patients in different societies.
Obsesif kompulsif bozukluk hastalarında triptofanhidroksilaz gen polimorfizmi
Keywords: obsessive compulsive disorder; tryptophan hydroxylase gene; polymorphism